The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.organomet.9b00599
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization of 1-Butene to 2-Butene Catalyzed by Metal–Organic Frameworks

Abstract: MIL-100 and MIL-101 were synthesized and evacuated to generate a series of heterogeneous catalysts for isomerization of 1-butene. Their crystal structures and pore properties were characterized by PXRD and nitrogen adsorption−desorption techniques. These catalysts showed high catalytic activity for isomerization of 1-butene and high selectivities for 2-butene at room temperature. Moreover, the MIL-101 (Cr) catalyst evacuated at 200 °C exhibited the largest BET surface area of 2759 m 2 g −1 . At the same time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In all cases, it has been proposed that the zirconium framework has improved catalytic activity through physical means, such as site isolation, , nanoparticle size control, ,, and shape selectivity. , However, to the best of our knowledge, no work has shown olefin hydrogenation activity intrinsic to the Zr-MOFs themselves. Fewer studies have focused on olefin isomerization in MOFs, , and for Zr-MOFs, olefin isomerization has only been reported on sulfated nodes, which possess strong Brønsted acid sites. , Collectively, the current MOF catalyst literature suggests that the unmodified metal-oxide nodes of Zr-MOFs are spectators or inactive in catalytic olefin transformations such as OHI.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, it has been proposed that the zirconium framework has improved catalytic activity through physical means, such as site isolation, , nanoparticle size control, ,, and shape selectivity. , However, to the best of our knowledge, no work has shown olefin hydrogenation activity intrinsic to the Zr-MOFs themselves. Fewer studies have focused on olefin isomerization in MOFs, , and for Zr-MOFs, olefin isomerization has only been reported on sulfated nodes, which possess strong Brønsted acid sites. , Collectively, the current MOF catalyst literature suggests that the unmodified metal-oxide nodes of Zr-MOFs are spectators or inactive in catalytic olefin transformations such as OHI.…”
Section: Introductionmentioning
confidence: 99%
“…The isomerization of primary B1 to secondary B2 has practical importance as it influences the distribution of final products. This process has attracted extensive study from both commercial and fundamental perspectives. However, precisely identifying the isomerization pathway within the context of BD hydrogenation poses technical challenges. The main difficulty lies in determining whether B2 forms directly from BD hydrogenation or via B1 isomerization.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to synthesize single-site catalysts include the surface organometallic chemistry (SOMC) approach and the use of metal–organic and covalent organic frameworks (MOFs and COFs, respectively), and both have had limited success with alkene isomerization. Estes demonstrated that an alumina-supported platinum-hydride is effective at 1-hexene isomerization (Figure b, bottom right), and a handful of examples of MOFs show activity for 1-butene isomerization and E / Z isomerization. While these advancements demonstrate the potential of single-site catalysts in alkene isomerization, their substrate scopes are highly limited and often utilize precious metals as the active site.…”
Section: Introductionmentioning
confidence: 99%